Ecologia do pastejo de cordeiras em pastagem de azevém e trevo vermelho sob intensidades de desfolha - Glienke, Carine Lisete (2009)
In the period May-November 2007 experiment was conducted in an area of the Federal University of Santa Maria, was studied the relationship between the pasture dynamics and the ingestive behavior of lambs, grazing Italian ryegrass (Lolium multiflorum Lam.) and red clover (Trifolium pratense L.) pasture under different defoliation intensities. Rotational grazing was used and the interval between grazing cycle was determined by the thermal sum of 313 degree-days. The evaluations of ingestive behavior were made by visual observation, in four continuous periods of 24 hours. The values of disappearance of the initial sward height were 65 ( very high ), 58 ( high ), 47 ( mean ) and 37% ( low ), respectively, showing the defoliation intensities. The sward vertical structure was similar among defoliation intensities. The forage allowance decreased linearly as the defoliation intensities increased. For each percent on the forage allowance, there were a decreasing of 0.35 on bite/minute. Bite rate and the number of bites/feeding station were reduced by the diminution of the leaf contribution on the pasture structure, resulting the cycle of pasture, accompanied by the increase of NDF and decrease of CP levels of the forage ingested by lambs. The change of pasture phonological stage proved to be more important than the defoliation intensities tested to cause changes in displacement patterns and feeding stations of lambs.